A CHEMICAL/GAS PLUME TRACING ROBOT SIMULATOR FOR QUADROTOR PLATFORMS: A MODIFIED GAUSSIAN-MEANDERING PLUME PROPAGATION MODEL - Eu, Kok Seng; Yap, Kian Meng (Malaysian Journal of Computer Science, 2019)
The process of evaluating the performance of chemical/gas plume tracing (CPT) algorithms is difficult because of real-world environmental parameters (i.e. surrounding wind) that are beyond researchers’ control, therefore, a CPT simulator can be useful. In this study, we design a modified Gaussian-meandering plume propagation model that is enhanced with the realistic characteristics of plume propagation such as meandering, internal intermittency, and vortices, which have not been modelled in the previous studies before. Subsequently, we use a computational fluid dynamics (CFD) software to generate the three-dimensional (3D) wind vectors and study the impact of quadrotor’s propellers, and then incorporating into the plume propagation design. On the whole, the study presented a complete CPT simulator for quadrotor platform with the realistic characteristics of plume propagation.